Rubber composition
The rubber composition, featuring diene rubber with natural rubber, unsaturated fatty acids, and cobalt fatty acid cobalt salt, addresses the challenge of achieving high moisture-resistant heat adhesion to steel cords, thereby enhancing tire durability and performance.
Patent Information
- Application Number
- JP2021023094
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-04
- Filing Date
- 2021-02-17
- Publication Date
- 2025-04-03
- Estimated Expiration
- 2041-02-17
AI Technical Summary
Existing rubber compositions for tires do not adequately achieve high moisture-resistant heat adhesion to steel cords, which is crucial for tire durability and performance.
A rubber composition comprising 100 parts by mass of diene rubber with 50% or more natural rubber, 1 to 10 parts by mass of unsaturated fatty acids with 11 or more carbon atoms, and 0.01 to 2.0 parts by mass of cobalt fatty acid cobalt salt, which enhances the moisture-resistant heat adhesion to steel cords.
The rubber composition significantly improves the moisture-resistant heat adhesion to steel cords, leading to enhanced tire durability and performance, particularly in terms of long-term adhesion and resistance to moisture and heat.
Smart Images

Figure 0007656171000001 
Figure 0007656171000002 
Figure 0007656171000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a rubber composition having excellent adhesion to steel cords due to moisture and heat resistance. [Background technology]
[0002] The rubber material that constitutes tires is often reinforced with steel cords. In such rubber materials, it is necessary to strengthen the adhesion between the rubber and the steel cords to increase durability. In particular, in order to manufacture high-quality tires more stably, there is a demand to further improve not only the initial adhesion between the rubber and the steel cords, but also their long-term adhesion and adhesion resistance to moisture and heat.
[0003] For example, Patent Document 1 proposes that a compounded composition obtained by adding 0.5 to 10 parts by weight of a primary fatty acid having 6 to 10 carbon atoms and / or a metal salt thereof to 100 parts by weight of a rubber component improves the corrosion fatigue resistance and durability life of a steel cord. Also, for example, Patent Document 2 discloses a rubber composition containing a diene rubber, cobalt benzoate, and rosin and / or a derivative thereof, and proposes improvements in initial adhesion and moisture and heat resistant adhesion. However, with the increasing performance of tires, there is a demand for a rubber composition that has excellent moisture and heat resistant adhesion to steel cords. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 58-161604 [Patent Document 2] JP 2007-99868 A Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a rubber composition having improved adhesion to steel cords against heat and humidity above the conventional level. [Means for solving the problem]
[0006] The rubber composition of the present invention that achieves the above object is characterized by containing 100 parts by mass of diene rubber containing 50% by mass or more of natural rubber, 1 to 10 parts by mass of an unsaturated fatty acid having 11 or more carbon atoms, and 0.01 to 2.0 parts by mass of a fatty acid cobalt salt in terms of cobalt amount. Effect of the Invention
[0007] The rubber composition of the present invention contains 100 parts by mass of diene rubber containing 50% by mass or more of natural rubber, 1 to 10 parts by mass of unsaturated fatty acid having 11 or more carbon atoms, and 0.01 to 2.0 parts by mass of fatty acid cobalt salt in terms of cobalt content, so that the moisture and heat resistant adhesion to steel cord can be improved to a level higher than that of conventional rubber.
[0008] The fatty acid cobalt may be cobalt stearate. The number of moles of the unsaturated fatty acid in the rubber composition (M UFA ) and the number of moles of stearic acid (M SA ) ratio (M UFA / M SA ) should be 0.2 to 5.0.
[0009] In the rubber composition, the unsaturated fatty acid having 11 or more carbon atoms is preferably a rosin resin. The rosin resin preferably has an acid value of 50 to 200 KOHmg / g and a softening point of 60 to 110°C, which can provide better heat and moisture resistant adhesion.
[0010] The rubber composition preferably contains 1 to 10 parts by mass of the unsaturated fatty acid having 11 or more carbon atoms, and the unsaturated fatty acid having 11 or more carbon atoms is preferably an unsaturated fatty acid having 16 or more and less than 20 carbon atoms, which can provide better moisture and heat resistant adhesion.
[0011] In addition, 100 parts by mass of diene rubber is mixed with a nitrogen adsorption specific surface area of 20 to 99 m 2 It is preferable that the composition contains 40 to 140 parts by mass of carbon black and / or silica, and this can provide better heat and moisture resistant adhesion. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The diene rubber constituting the rubber composition of the present invention necessarily contains natural rubber. The inclusion of natural rubber improves the rubber strength. The natural rubber is contained in 50% by mass or more, preferably 50 to 100% by mass, more preferably 80 to 100% by mass, of 100% by mass of the diene rubber. If the natural rubber is less than 50% by mass, the rubber strength decreases and the possibility of separation becoming the starting point increases. The natural rubber is not particularly limited, and may be at least one selected from unmodified natural rubber and modified natural rubber (modified natural rubber) that are usually used in rubber compositions. When both unmodified natural rubber and modified natural rubber are contained, the total of the two may be 50% by mass or more.
[0013] The diene rubber may contain other diene rubbers other than natural rubber. Examples of other diene rubbers include isoprene rubber, butadiene rubber, styrene-butadiene rubber, styrene-isoprene rubber, styrene-isoprene-butadiene rubber, acrylonitrile-butadiene rubber, and butyl rubber. Among these, butadiene rubber and styrene-butadiene rubber are preferred. These other diene rubbers may be unmodified, but may also be modified diene rubbers in which the terminals and / or side chains of the molecular chain are modified with epoxy groups, carboxy groups, amino groups, hydroxy groups, alkoxy groups, silyl groups, amide groups, or the like.
[0014] The rubber composition contains a fatty acid cobalt salt. By blending the fatty acid cobalt salt, the adhesion of the rubber composition to the steel cord can be improved. In addition, by blending the fatty acid cobalt salt together with an unsaturated fatty acid having 11 or more carbon atoms, the wet heat resistance adhesion of the rubber composition to the steel cord can be improved, and in particular, the long-term adhesion can be excellent from a practical standpoint.
[0015] The fatty acid cobalt salt is blended so that the amount of cobalt is 0.01 to 2.0 parts by mass relative to 100 parts by mass of the diene rubber. The amount of cobalt is preferably 0.05 to 1.0 parts by mass, more preferably 0.1 to 0.5 parts by mass. If the amount of fatty acid cobalt salt blended is less than 0.01 parts by mass in terms of cobalt, the adhesion of the rubber composition to the steel cord cannot be sufficiently improved. If the amount of cobalt exceeds 2.0 parts by mass, the adhesion under moist heat is rather reduced. Furthermore, the hardness of the rubber composition becomes excessively high.
[0016] The fatty acid constituting the fatty acid cobalt salt may be either a saturated fatty acid or an unsaturated fatty acid, and may be either a linear or branched fatty acid. Furthermore, in this specification, the fatty acid of the fatty acid cobalt salt may be an alicyclic compound forming a ring other than an aromatic ring. Examples of the fatty acid cobalt salt include cobalt stearate, cobalt palmitate, cobalt octenate, cobalt naphthenate, cobalt neodecanoate, cobalt trineodecanoate borate, and cobalt rosinate. Among them, cobalt stearate and cobalt trineodecanoate borate are preferred, and by using them in combination with an unsaturated fatty acid having 11 or more carbon atoms, the rubber composition can be made excellent in terms of wet heat resistance adhesion to steel cord, particularly long-term adhesion from a practical standpoint.
[0017] The rubber composition contains an unsaturated fatty acid having 11 or more carbon atoms. By blending the unsaturated fatty acid having 11 or more carbon atoms together with the fatty acid cobalt salt described above, the adhesion of the rubber composition to the steel cord, particularly the moisture and heat resistant adhesion, can be improved. The unsaturated fatty acid having 11 or more carbon atoms reacts with the amine component in the rubber composition to inhibit the amine component from destroying the adhesive layer, and the adhesion, particularly the moisture and heat resistant adhesion, can be maintained and improved. The amine component in the rubber composition is thought to be derived from a vulcanization accelerator, etc.
[0018] The unsaturated fatty acid having 11 or more carbon atoms is blended in an amount of 1 to 10 parts by mass per 100 parts by mass of diene rubber. Preferably, the unsaturated fatty acid having 11 or more carbon atoms is blended in an amount of 1 to 8 parts by mass, more preferably 1 to 6 parts by mass, and even more preferably 2 to 5 parts by mass. If the unsaturated fatty acid having 11 or more carbon atoms is less than 1 part by mass, the wet heat resistance adhesion of the rubber composition to the steel cord cannot be sufficiently improved. If it exceeds 10 parts by mass, the hardness of the rubber composition decreases. In addition, when the rubber composition contains unsaturated fatty acid cobalt, the total amount of cobalt in the unsaturated fatty acid cobalt and the fatty acid cobalt is within the above-mentioned range, and the total amount of the unsaturated fatty acid and the unsaturated fatty acid having 11 or more carbon atoms in the unsaturated fatty acid cobalt is within the above-mentioned range.
[0019] The number of moles of unsaturated fatty acid in the rubber composition (M UFA ) and the number of moles of stearic acid (M SA ) ratio (M UFA / M SA ) is preferably 0.2 to 5.0. As described above, the unsaturated fatty acid in the rubber composition is the sum of the unsaturated fatty acid having 11 or more carbon atoms and the unsaturated fatty acid when the unsaturated fatty acid cobalt is included. The stearic acid in the rubber composition is the sum of the stearic acid when the fatty acid cobalt is cobalt stearate and the stearic acid when the unsaturated fatty acid having 11 or more carbon atoms is stearic acid.
[0020] The number of moles of unsaturated fatty acid in the rubber composition (M UFA ) and the number of moles of stearic acid (M SA ) ratio (M UFA / M SA When the molar ratio (M) is 0.2 or more, the adhesiveness against heat and moisture can be ensured. When the molar ratio (M) is 5.0 or less, the rubber hardness can be ensured. UFA / M SA ) is more preferably 0.5 to 4.0.
[0021] As the unsaturated fatty acid having 11 or more carbon atoms, rosin resin is preferred. Rosin resin is a natural resin mainly composed of rosin acids such as abietic acid (20 carbon atoms, 2 unsaturated bonds), palustric acid (20 carbon atoms, 2 unsaturated bonds), isopimaric acid (20 carbon atoms, 2 unsaturated bonds), neoabietic acid (20 carbon atoms, 2 unsaturated bonds), and levopimaric acid (20 carbon atoms, 2 unsaturated bonds). These rosin acid components react with the amine components in the rubber composition, thereby suppressing the amine components from affecting the adhesion properties against heat and moisture. The amine components in the rubber composition are considered to be derived from vulcanization accelerators, etc. Examples of rosin resins include gum rosin, wood rosin, and tall rosin. The rosin resin may be a rosin modification such as an unsaturated carboxylic acid modified rosin resin such as maleic acid, an esterified rosin resin, an esterified maleic acid modified rosin resin, a rosin modified phenolic resin, an amide compound of rosin, an amine salt of rosin, or a metal salt of rosin acid such as cobalt rosinate. Rosin resin is also called an unsaturated resin acid. In this specification, the unsaturated fatty acid having 11 or more carbon atoms includes rosin resin.
[0022] The acid value of the rosin resin is not particularly limited, but is preferably 50 to 200 KOHmg / g, and more preferably 80 to 160 KOHmg / g. When the acid value of the rosin resin is 50 KOHmg / g or more, the decrease in hardness of the rubber composition can be suppressed. When the acid value is 200 KOHmg / g or less, the increase in hardness of the rubber composition can be suppressed. The acid value of the rosin resin can be determined in accordance with JIS K5902.
[0023] The softening point of the rosin resin is not particularly limited, but is preferably 60 to 110°C, and more preferably 70 to 110°C. When the softening point of the rosin resin is 60°C or higher, the decrease in high-temperature hardness can be suppressed. When the softening point is 110°C or lower, the high-temperature viscosity can be reduced, and processability can be improved. The softening point of the rosin resin can be determined in accordance with JIS K5902.
[0024] The unsaturated fatty acid having 11 or more carbon atoms has at least one unsaturated bond, and preferably has 1 to 2 unsaturated bonds. The unsaturated fatty acid also has 11 or more carbon atoms, and preferably has 16 or more but less than 20 carbon atoms.
[0025] Examples of unsaturated fatty acids with 11 or more carbon atoms include myristoleic acid (14 carbon atoms, 1 unsaturated bond), palmitoleic acid (16 carbon atoms, 1 unsaturated bond), oleic acid (18 carbon atoms, 1 unsaturated bond), elaidic acid (18 carbon atoms, 1 unsaturated bond), vaccenic acid (18 carbon atoms, 1 unsaturated bond), gadoleic acid (20 carbon atoms, 1 unsaturated bond), eicosenoic acid (20 carbon atoms, 1 unsaturated bond), erucic acid (22 carbon atoms, 1 unsaturated bond), and nervonic acid (20 carbon atoms, 1 unsaturated bond). Examples of such fatty acids include linoleic acid (18 carbon atoms, 2 unsaturated bonds), eicosadienoic acid (20 carbon atoms, 2 unsaturated bonds), docosadienoic acid (22 carbon atoms, 2 unsaturated bonds), linolenic acid (18 carbon atoms, 3 unsaturated bonds), pinolenic acid (18 carbon atoms, 3 unsaturated bonds), eleostearic acid (18 carbon atoms, 3 unsaturated bonds), mead acid (20 carbon atoms, 3 unsaturated bonds), eicosatrienoic acid (20 carbon atoms, 3 unsaturated bonds), stearidonic acid (18 carbon atoms, 4 unsaturated bonds), etc. Among these, unsaturated fatty acids having 16 to 20 carbon atoms are preferred.
[0026] The rubber composition may contain carbon black and / or silica. By compounding carbon black and / or silica, the mechanical properties of the rubber composition can be improved.
[0027] Examples of silica include wet silica (hydrated silicic acid), dry silica (anhydrous silicic acid), calcium silicate, and aluminum silicate, which may be used alone or in combination of two or more. The CTAB adsorption specific surface area of silica is not particularly limited, but is preferably 100 to 250 m 2 / g, more preferably 120 to 200m 2 / g. The CTAB adsorption specific surface area of silica is 100m 2By making the CTAB adsorption specific surface area of the silica 250 m / g or more, the abrasion resistance of the rubber composition can be ensured. 2 By making the CTAB specific surface area of silica equal to or less than 1 / g, it is possible to improve wet performance and low rolling resistance. In this specification, the CTAB specific surface area of silica is a value measured according to ISO 5794.
[0028] Examples of carbon black include furnace carbon black such as FEF, GPF, HMF, and SRF, which may be used alone or in combination of two or more. The nitrogen adsorption specific surface area of carbon black is not particularly limited, but is preferably 20 to 99 m. 2 / g, more preferably 40 to 99m 2 / g. The nitrogen adsorption specific surface area of carbon black is preferably 20 m 2 By increasing the nitrogen adsorption specific surface area of carbon black to 99 m / g or more, the mechanical properties of the rubber composition can be ensured. 2 / g or less, low heat buildup can be ensured. In this specification, the nitrogen adsorption specific surface area of carbon black is measured in accordance with JIS K6217-2.
[0029] The amount of carbon black and / or silica to be compounded is preferably 40 to 140 parts by mass, more preferably 50 to 130 parts by mass, based on 100 parts by mass of diene rubber. By making the amount of carbon black and silica 40 parts by mass or more, the mechanical properties of the rubber composition can be improved. Also, by making the amount 140 parts by mass or less, low heat buildup can be ensured.
[0030] In the present invention, it is preferable to compound a silane coupling agent together with silica. By compounding a silane coupling agent, the dispersibility of silica in diene rubber can be improved, and mechanical properties can be further improved. The type of silane coupling agent is not particularly limited as long as it can be used in a rubber composition containing silica, and examples of the silane coupling agent include sulfur-containing silane coupling agents such as bis-(3-triethoxysilylpropyl) tetrasulfide, bis(3-triethoxysilylpropyl) disulfide, 3-trimethoxysilylpropyl benzothiazole tetrasulfide, γ-mercaptopropyl triethoxysilane, and 3-octanoylthiopropyl triethoxysilane.
[0031] The amount of the silane coupling agent is preferably 3 to 15 mass % relative to the mass of silica, and more preferably 5 to 10 mass %. When the amount of the silane coupling agent is 3 mass % or more of the silica amount, the dispersion of the silica can be improved. When the amount is 15 mass % or less, the condensation of the silane coupling agent itself can be suppressed, and the rubber composition can be given the desired hardness and strength.
[0032] The rubber composition may contain inorganic fillers other than carbon black and silica. Examples of the inorganic fillers include calcium carbonate, magnesium carbonate, talc, clay, alumina, aluminum hydroxide, titanium oxide, and calcium sulfate. These may be used alone or in combination of two or more.
[0033] The rubber composition of the present invention may contain various additives that are generally used in rubber compositions, such as vulcanizing or crosslinking agents, vulcanization accelerators, antioxidants, plasticizers, processing aids, and thermosetting resins, within the range that does not impair the object of the present invention. Moreover, such additives may be kneaded in a general manner to prepare a rubber composition, which can then be used for vulcanization or crosslinking. The amount of these additives may be a conventional amount, as long as it does not violate the object of the present invention. The rubber composition may be produced by mixing the above-mentioned components using a general rubber kneading machine, such as a Banbury mixer, kneader, roll, etc.
[0034] The rubber composition of the present invention is suitable for forming a component having a steel cord. A tire having a component in which a steel cord is coated with the rubber composition of the present invention has excellent adhesion between the steel cord and rubber, particularly excellent adhesion under wet heat and long-term adhesion, and can improve tire durability to a level higher than that of conventional tires.
[0035] The present invention will be further described below with reference to examples, but the scope of the present invention is not limited to these examples. EXAMPLES
[0036] In preparing 34 types of rubber compositions (Examples 1 to 19, Standard Examples, Comparative Examples 1 to 14) shown in Tables 1 to 4 having the common composition shown in Table 5, the components except for sulfur and vulcanization accelerator were kneaded in a 1.7 L Banbury mixer for 5 minutes, and when the temperature reached 145°C, the components were released to form a master batch. Sulfur and vulcanization accelerator were added to the obtained master batch, and the mixture was kneaded in an open roll at 70°C to obtain 30 types of rubber compositions. The compounding amount of the common composition shown in Table 5 is expressed as parts by mass relative to 100 parts by mass of the diene rubber shown in Tables 1 to 4.
[0037] Rubber Hardness The obtained rubber composition was vulcanized at 170°C for 10 minutes using a mold of a given shape (inner dimensions: length 150 mm, width 150 mm, thickness 2 mm) to prepare a vulcanized rubber test piece. Using the obtained vulcanized rubber test piece, the rubber hardness was measured at a temperature of 20°C using a type A durometer in accordance with JIS K6253. The obtained results are shown in the "rubber hardness" column of Tables 1 to 4 as an index with the result of the standard example being 100. A value of 90 or more and 120 or less is considered to be a pass level.
[0038] Adhesive properties and heat and moisture adhesion properties A plurality of steel cords arranged in parallel with each other at intervals of 12.7 mm were embedded in the obtained rubber composition with a length of 12.7 mm, and vulcanized at 160°C for 20 minutes to prepare a test sample. The test samples were divided into two groups, and one group was used to evaluate the initial adhesion, and the other group was used as a test sample that underwent an accelerated moist heat deterioration test at a temperature of 80°C and a relative humidity of 96% for 336 hours to evaluate the moist heat adhesion. For the initial adhesion and moist heat adhesion, a pull-out test of the steel cord was performed using each test sample in accordance with ASTM-D-2, and the coverage of the rubber on the pulled wire was visually determined. The obtained results are shown in the "initial adhesion" and "moisture and heat adhesion" columns of Tables 1 to 4 as an index with the result of the standard example being 100. The larger the index, the better the "initial adhesion" and "moisture and heat adhesion" to the steel cord. The index values of "initial adhesion" and "moisture and heat adhesion" of 100 or more are considered to be pass levels.
[0039] Overall tire durability (belt edge separation) The obtained rubber composition was used as a belt coat rubber to prepare pneumatic tires (size: 275 / 80R22.5). Each pneumatic tire was mounted on a standard rim (rim size 19.5-4.0), and the air pressure was set to 700 kPa. The tire was attached to an indoor drum tester, and the initial speed was set to 5 km / h, the initial load was set to 60% of the maximum load specified by JATMA, the speed was increased by 2 km / h every 36 hours, and the load was increased by 10% of the maximum load every 12 hours until it reached 120% of the maximum load. The running distance until the tire was destroyed was measured. The obtained results were judged based on the following criteria ◎, ◯, △, and ×, and are shown in the "Tire Overall Durability" column in Tables 1 to 4. ◎ and ◯ are acceptable levels. ◎: Mileage is 20% or more higher than the standard mileage 〇: Mileage is between +10% and +20% of the standard mileage △: Mileage is between -10% and +10% of the standard mileage ×: Mileage is less than -10% of the standard mileage
[0040] [Table 1]
[0041] [Table 2]
[0042] [Table 3]
[0043] [Table 4]
[0044] The types of raw materials used in Tables 1 to 4 are shown below. NR: Natural rubber, STR20 SBR: Styrene-butadiene rubber, Zeon Corporation NIPOL 1502 Carbon black: Cabot Japan's Show Black N330T, nitrogen adsorption specific surface area is 72m 2 / g Silica: ULTRASIL VN3GR manufactured by EVONIK SILICA, CTAB specific surface area is 160m 2 / g Petroleum resin: Tonex Corporation Escoretz 1102 Terpene resin: Yasuhara Chemical Co., Ltd. YS Resin TO-125 Gum rosin: China rosin WW manufactured by Arakawa Chemical Industries, Ltd., acid value = 173KOHmg / g, softening point = 87℃ Maleic acid modified rosin: Malkid 382 manufactured by Arakawa Chemical Industries, Ltd., acid value = 107 KOHmg / g, softening point = 105°C Stearic acid: NOF Corporation beads stearic acid YR Cobalt stearate: Cobalt stearate manufactured by DIC, with a cobalt content of 10% by mass Cobalt oleate: Mitsuwa Chemical Co., Ltd., cobalt content 10% by mass Cobalt trineodecanoate borate: DICNATE NBC-2 manufactured by DIC, with a cobalt content of 22% by mass Cobalt rosinate: Cobalt rosinate manufactured by Airec, with a cobalt content of 10% by mass Cobalt naphthenate: Cobalt naphthenate manufactured by DIC, with a cobalt content of 10% by mass Oleic acid: manufactured by Tokyo Chemical Industry Co., Ltd. Linoleic acid: manufactured by Tokyo Chemical Industry Co., Ltd. Palmitoleic acid: manufactured by Tokyo Chemical Industry Co., Ltd.
[0045] [Table 5]
[0046] The types of raw materials used in Table 5 are shown below. Zinc oxide: Three types of zinc oxide manufactured by Seido Chemical Industry Co., Ltd. Anti-aging agent: Flexis 6PPD Insoluble sulfur: Shikoku Chemical Industry Co., Ltd. Myucron OT-20F Vulcanization accelerator: Noccela CZ-G manufactured by Ouchi Shinko Chemical Industry Co., Ltd.
[0047] As is clear from Tables 1 to 4, it was confirmed that the rubber compositions of Examples 1 to 19 improved the heat and moisture adhesion to levels higher than those of conventional rubber compositions while maintaining the rubber hardness.
[0048] The rubber composition of Comparative Example 1 does not contain an unsaturated fatty acid having 11 or more carbon atoms, and therefore the effect of improving the adhesion under wet heat is smaller than that of the Examples. The overall tire durability is poor (Δ). In the rubber composition of Comparative Example 2, the unsaturated fatty acid having 11 or more carbon atoms is less than 1 part by mass, so the effect of improving the adhesion under wet heat is smaller than that of the Examples. The overall tire durability is poor (Δ). The rubber compositions of Comparative Examples 3 and 4 do not contain an unsaturated fatty acid having 11 or more carbon atoms, and therefore cannot improve the adhesiveness under wet heat. The overall tire durability is poor (Δ). In the rubber composition of Comparative Example 5, the amount of cobalt exceeds 2 parts by mass, so that the adhesiveness under heat and humidity is rather deteriorated. The overall tire durability is poor (Δ). The rubber composition of Comparative Example 6, which contains stearic acid instead of an unsaturated fatty acid having 11 or more carbon atoms, has poor adhesion under heat and humidity. The overall tire durability is poor (Δ). In the rubber compositions of Comparative Examples 7 and 8, the unsaturated fatty acid having 11 or more carbon atoms exceeds 10 parts by mass, so that the rubber hardness is significantly reduced, and the overall tire durability is poor (Δ). The rubber composition of Comparative Example 9, in which stearic acid was blended in place of the unsaturated fatty acid having 11 or more carbon atoms, had a lower heat and moisture adhesion than the control example. The rubber compositions of Comparative Examples 10 and 11 have less than 1 part by mass of unsaturated fatty acid having 11 or more carbon atoms, so that the adhesiveness under heat and humidity is not improved. The overall tire durability is poor (Δ). The rubber composition of Comparative Example 12 did not contain an unsaturated fatty acid having 11 or more carbon atoms, but contained an unsaturated fatty acid cobalt. However, the total amount of unsaturated fatty acids was small, and the adhesiveness under wet heat was not improved. In the rubber composition of Comparative Example 13, the amount of cobalt exceeds 2 parts by mass, and therefore the adhesiveness under moist heat is rather deteriorated. In the rubber composition of Comparative Example 14, the amount of unsaturated fatty acid having 11 or more carbon atoms exceeds 10 parts by mass, so that the rubber hardness is reduced.
Claims
1. A rubber composition comprising 100 parts by mass of a diene rubber containing 50% by mass or more of natural rubber, 1 to 10 parts by mass of an unsaturated fatty acid having 11 to less than 20 carbon atoms, and 0.01 to 2.0 parts by mass of a fatty acid cobalt salt in terms of cobalt amount.
2. A rubber composition comprising 100 parts by mass of diene rubber containing 50% by mass or more of natural rubber, 1 to 10 parts by mass of an unsaturated fatty acid having 11 or more carbon atoms, and 0.01 to 2.0 parts by mass of a fatty acid cobalt salt in terms of cobalt content, said unsaturated fatty acid being selected from gum rosin, wood rosin, tall rosin, and unsaturated carboxylic acid modified rosin, and said fatty acid cobalt salt being selected from cobalt stearate, cobalt palmitate, cobalt octenoate, cobalt neodecanoate, and cobalt trineodecanoate borate.
3. 3. The rubber composition according to claim 1, wherein the fatty acid cobalt is cobalt stearate.
4. The number of moles of the unsaturated fatty acid in the rubber composition (M UFA ) and the number of moles of stearic acid (M SA ) ratio (M UFA / M SA 4. The rubber composition according to claim 3, wherein the value of (a) is 0.2 to 5.
0.
5. The rubber composition according to claim 2, wherein the unsaturated fatty acid has an acid value of 50 to 200 KOHmg / g and a softening point of 60 to 110°C.
6. The rubber composition according to claim 1 , wherein the unsaturated fatty acid has 16 or more and less than 20 carbon atoms.
7. A diene rubber having a nitrogen adsorption specific surface area of 20 to 99 m is mixed with 100 parts by mass of diene rubber. 2 7. The rubber composition according to claim 1, further comprising 40 to 140 parts by mass of carbon black and / or silica.
Citation Information
Patent Citations
Radial tire
JP1983161604A
Method for bonding galvanized steel cord to rubber and conveyer belt made by using the method
JP1999021389A
Rubber composition for tire tread
JP2006328107A
Rubber composition, rubber-metal composite using the same, and pneumatic tire
JP2007099868A
Rubber composition for coating steel cord
JP2010059234A